SERVICE BAWAH BOLA VOLI MELALUI PENDEKATAN BERMAIN LEMPAR TANGKAP DI SMPN 1 NANGA MAHAP - Winarka, Heri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The aim of the research to improve learning outcomes under the service toss a volleyball to play catch. Forms of research is classroom action research. In a classroom action research this is the subject of this study were teachers collaborate with students of SMPN 1 Nanga Mahab Sekadau totaling 30 students. Based on the results of research carried out research have a positive impact on students because it consists of the first cycle and the second cycle of planning, implementation, observation and reflection. Learning first cycle of students who have recently graduated amounted to 14 students or 66.7%, while the students who have not passed amounted to 7 students or 33.3%, then proceed to the second cycle so that students have the opportunity to repair using throwing catch with such movements can thus serve categorized by graduate students numbered 30 students and the student has not passed a numbered 0. Keywords: Service Down, Throw Capture